Isolation and identification of microbial load from the dried Chanda fish, Chanda nama (Hamilton, 1822) (Jahangirnagar University Journal of Biological Sciences, 2025)
The present study was conducted to determine the bacterial load, isolate, and identify the bacteria from the dried Chanda fish, Chanda nama (Hamilton, 1822). 20 dry fish samples were collected from two different districts: Mymensingh (Nowmohal fish market) and Dhaka (Kawran Bazar fish market); 10 raw fish samples were collected from the Dhaka Kawran Bazar fish market, dried at home (control) to compare them with the quality of commercially dried fish of different districts. In this study, the total bacterial counts (TBC) and total yeast mold counts (TYMC) were recorded in different dilutions. Bacterial isolation and identification were accomplished by analyzing the cultural, staining, and biochemical characteristics of each sample, which were separated into three sections (head, body, and tail). The results varied among fish samples from different districts. The highest bacterial load was found in the home-made dried fish samples which were collected alive from Dhaka (TBC was uncountable in 1st, 2nd, 3rd dilutions and 4th dilution it was 5.5 × 102 cfu/gm) followed by medium load in the sample of Dhaka (Uncountable in 1st and 2nd dilution but in 3rd and 4th dilution it was 7.8×103 cfu/gm and 5.4 × 102 cfu/gm respectively) and lowest load in the sample of Mymensingh (1st, 2nd dilution was uncountable and 3rd and 4th dilution containing 5.3 × 103 cfu/gm and 2.5 × 102 cfu/gm respectively). As the density of bacterial colonies was overlapped in the first two dilutions and uncountable, these two dilution related data were excluded from the analyses. The analysis shown here is based on those dilutions with countable separate colonies. Again, the highest load of yeast and mold was observed in the home-made fish sample (for 1st and 2nd dilutions it was uncountable), but medium in the fish sample of Mymensingh (for 1st dilution uncountable but in the 2nd dilution it was 2.2 × 103 cfu/gm) and lowest in the sample of Dhaka (for 1st and 2nd dilution 3.16 × 104 cfu/gm and 2.0 × 103 cfu/gm respectively). Pathogenic bacteria like Salmonella spp., Pseudomonas spp., and Staphylococcus spp. were detected in all the fish samples of dried C. nama, which could indicate unhygienic drying processes. Raoultella planticola, a pathogenic bacterium, was identified from the home-made sample using the Biolog software. This study highlights that home-dried Chanda fish samples harbored higher bacterial loads than commercially dried ones, potentially due to a lack of preservatives such as pesticides, which are commonly used in commercial fish drying. These findings underscore the need for improved hygiene and safety measures in traditional fish drying methods to ensure public health safety.Jahangirnagar University J. Biol. Sci. 13(1 & 2): 41-53, 2024 (June & December)